2019
DOI: 10.1001/jamanetworkopen.2019.7136
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicaid Expansion With Health Insurance Coverage Among Persons With a Disability

Abstract: Key Points Question Was the Patient Protection and Affordable Care Act Medicaid expansion associated with an increase in health insurance coverage among persons with a disability? Findings In this cross-sectional analysis of more than 2.5 million US adults aged 26 to 64 years with incomes up to 138% of the federal poverty level, Medicaid expansion was significantly associated with lower uninsurance rates and higher Medicaid and private insurance coverage fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
(103 reference statements)
2
23
0
Order By: Relevance
“…We find that, in the post-ACA era, there are still unmet needs for working-age adults with a disability, in general, but that individuals with a disability who are receiving federal disability benefits have improved access over those who are not. Our results are consistent with pre-ACA findings that individuals with a disability who are receiving federal disability benefits have improved access to care (Livermore et al, 2009), but that this difference persists even after an overall increase in health care access and utilization for all individuals with a disability in the ACA era (Kennedy et al, 2017; Stimpson et al, 2019). In 2018, approximately 9 and 5 million individuals aged 18–64 were enrolled in the SSDI and SSI programs, respectively (Social Security Administration, 2019a, 2019e).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We find that, in the post-ACA era, there are still unmet needs for working-age adults with a disability, in general, but that individuals with a disability who are receiving federal disability benefits have improved access over those who are not. Our results are consistent with pre-ACA findings that individuals with a disability who are receiving federal disability benefits have improved access to care (Livermore et al, 2009), but that this difference persists even after an overall increase in health care access and utilization for all individuals with a disability in the ACA era (Kennedy et al, 2017; Stimpson et al, 2019). In 2018, approximately 9 and 5 million individuals aged 18–64 were enrolled in the SSDI and SSI programs, respectively (Social Security Administration, 2019a, 2019e).…”
Section: Discussionsupporting
confidence: 88%
“…Additional research is necessary to explore the root causes of these differences in health care access and utilization, which would help toward the policy goal of equitable access to health care for all individuals with disabilities. Our research and related studies (Kennedy et al, 2017; Stimpson et al, 2019) make clear that although ACA insurance expansions have improved health care access for individuals with disabilities, these expansions alone are not enough to ensure that all individuals with disabilities have sufficient access. Continuing to research different subgroups within the population of individuals with disabilities, such as we have done here with the population receiving federal disability benefits, may identify high priority populations and policy levers.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We used the triple-differences approach to isolate the independent association of the CJR model with THR or TKR use. 32 , 33 We addressed the violation of the parallel trends assumptions for the triple-differences models by including interactions of the year with MSAs with the CJR model or MSAs without the CJR model and race/ethnicity dual-eligibility indicators (eMethods 2 in the Supplement ). 34 , 35 , 36 We obtained the adjusted estimated probabilities from these regression models and used tests for linear combinations to examine the hypotheses.…”
Section: Methodsmentioning
confidence: 99%
“… 9 McInerney, Mellor, and Sabik found that the ACA Medicaid expansion increased the share of Medicare enrollees with secondary Medicaid coverage, 10 and Stimpson and colleagues found positive Medicaid enrollment effects for disabled adults who were likely eligible prior to ACA expansion. 11 None of these studies examined outcomes other than insurance coverage for previously eligible populations, however.…”
Section: Introductionmentioning
confidence: 99%